Factors contribute to customer awareness towards Takaful Mesra product at Etiqa Insurance and Takaful Seremban Branch / Khairunnisa Mohamad - Mohamad, Khairunnisa (Faculty of Business and Management, 2011)
Etiqa Insurance and Takaful Berhad offer many types of product for General and Life Insurance. This study is designed to identify the factors that contribute the customer awareness of customer towards Takaful Mesra, one of Etiqa’s life products. Among those products, Takaful Mesra is most preferable product for customer. Thus, researcher would like to identify the probable factors contribute to customer awareness towards Takaful Mesra. Product knowledge, level of income and promotional tools are the independent variables while the main focus or the dependent variable is the customer awareness. The data being interpret by using SPSS and for research design using descriptive and exploratory research. Data of number policyholder for Takaful Mesra is within 2005 to 2010. Based on the finding result, shows there is a relationship between all variable with the customer awareness and also there has significant relationship with the dependent variable.